Evaluating the efficiency of surface treatment on plastic film PP, PE, PVC by cold plasma - Thai , Van Phuoc; Tran , Ngoc Dam; Duong, Khoa Nam (Journal of Technical Education Science, 2016)
Before printing, gluing and coating, plastic films having low surface energy like PP, PE, PVC, PA must be pretreated to increase adhesive quality. Current pretreatment methods, e.g. using flame or chemical solution have problems such as waste energy, polluting environment, difficulty adjusting. In this paper, a surface treatment model utilizing cold plasma at atmospheric pressure has been designed and experiments on plastic films PP, PE, PVC have been carried out. The advantages of the model are non-using chemical solution, easy control (adjustable input power). The results of experiments show that surface adhesion of pretreated plastic film is clearly improved (contact angle reduces under 88o after plasma treatment) with supplied power-225Wh (150v, 1.5A), treated width -150mm and treatment duration -3s/m.